Perceived Benefit, Environmental Concern and Sustainable Customer Behavior on Technology Adoption - Nanggong, Ardiwansyah; Rahmatia, Rahmatia (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. Environmentally friendly practices in the business sector for more targeting corporations as economic actors. However, the contribution of environmental sustainability cannot only encouraged by the firm but also the consumer’s participation. The eco-friendly behavior that arises from the adoption of technology by consumers is often influenced by various opposite motives. Perceived benefit is often regarded as a pragmatic motif because it is utilitarian while the environmental concern is interpreted as a form of altruism. This study aims to investigate the relevance of perceived benefit and environmental concern in the adoption of e-ticketing technology (paperless) and the dominant motive that influences consumers' sustainable behavior in adopting the technology. Data collection using paperless case (e-ticketing) to determine the motive of environmentally friendly behavior by consumers. There were 188 respondents who participated in the study. The study findings explain the importance and the corresponding conformity between the perceived benefits and the environmental concern of consumers in predicting sustainable consumer behavior in technology adoption.Keywords: Environmental concern, paperless, perceived benefit, sustainable consumer behavior, technology adoption